Characterization of relaxation processes in interacting vortex matter through a time-dependent correlation length. (8th September 2015) - Pleimling, Michel; Täuber, Uwe C
Abstract: Vortex lines in type-II superconductors display complicated relaxation processes due to the intricate competition between their mutual repulsive interactions and pinning to attractive point or extended defects. We perform extensive Monte Carlo simulations for an interacting elastic line model with either point-like or columnar pinning centers. From measurements of the space- and time-dependent height-height correlation function for lateral flux line fluctuations, we extract a characteristic correlation length that we use to investigate different non-equilibrium relaxation regimes. The specific time dependence of this correlation length for different disorder configurations displays characteristic features that provide a novel diagnostic tool to distinguish between point-like pinning centers and extended columnar defects.